Age of detection of congenital hearing loss in South Africa: A systematic review - Mukovhe Phanguphangu; Khomotjo Kgare; Andrew J. Ross (Journal of Public Health in Africa)
Background: Newborn hearing screening is the most important step towards early intervention of congenital or early-onset hearing loss (HL) and has the potential to optimise patient outcomes. Yet, literature on the age of identification of this HL in South Africa (SA) is sparse.